A Study of Covid-19 Relative Fatalities of the Abrahamic Religion Populations - Khodadoost, Baback (Journal of Quranic Sciences and Research, 2023)
More than three years statistics of the Covid-19 pandemic shows great anomalies in relative fatalities of different countries. Computations show that Christian and Jewish populations, by a factor of 4 to 5, suffer greater relative fatalities compared to the Muslim populations. Ironically, most Muslim populations are developing or underdeveloped, deprived of health services available to the mostly-developed Christian and Jewish populations. Factors that may be contributing to the fatality discrepancies such as, development status, median ages, and alcohol consumption rates, have been discussed. A Quranic forbiddance of drinking alcohol has been suggested as an important factor in the lower fatalities of the Muslim populations in Covid-19 pandemic.